Within the Law (of Hollywood). Gustav Machaty "in Services" of Metro-Goldwyn-Mayer - Hornicek, Jiri (Iluminace, 2006)
An analysis of Gustav Machaty's work during his second stay in the USA after 1936, focusing on the reconstruction of the making of the film Within the Law. The study is based on internal correspondence between MGM studio management and representatives of the Hays Censorship Office.
Keywords: Czech director; screenwriter and actor; MGM; emigrants; film production companies and studios; censorship